Gauvain Soleil Noyé - Jacques K. Noble-Kooijman (Anastasis: Research in Medieval Culture and Art)
The stature of the character of Gauvain in the novels of Chrétien de Troyes aroused number of studies which conclude in a degradation of the image of the hero the status of which seemed inviolable. It is not that with the Cart that a collection parallel to that of Lancelot, hero of the novel, is committed by Gauvain who fails straightaway in the Bridge under the water where he is close to the drowning and makes sorry figure. The appeal to a functional analysis of the structure of the novel leads to identify Gauvain as the false hero of the wonderful tales which had analyzed Propp. This analysis heuristics clarifies the intuitions of the previous critics which saw in Gauvain an anti-hero. The "sun of the chivalry" flooded in the water of the Bridge "Évage" made so by the tale of the Cart the origin wanted by Christian of this Gauvain's downgrading among the heroes as he makes act. The Cart is the novel-key of the evolution of the sense to be given to the chivalrous exploit as well as to worldly courtesy in the continuity of the work of the novelist champenois. Sense of Lancelot's adventures in the Cart is the proDrôme of the spiritual orientations of Perceval which relegate in the background the "ground" chivalries which illustrated Gauvain.